A Survey: How Periodontists and Other Dental Professionals View the Scope of Periodontics. Issue 7 (1st July 2014) - Chang, Peter K.; Hall, Joshua; Finkelman, Matthew; Park, Angel; Levi, Paul A.
Abstract : Background : How do periodontists think of themselves when they define their practices? How do other dental professionals view the scope of the specialty of periodontology? A strong component of periodontal residency programs is extracting teeth and preserving or building bony ridges for the eventual placement of implants. Has the discipline of periodontology moved away from retaining and treating the natural dentition? By the use of a rank‐order survey, the practice of periodontology was defined by periodontists and other dental professionals. Methods: In a pilot study, respondents were asked to list the answers to the question, "What is a periodontist?" The results were consolidated into eight statements. The eight statements were placed into an anonymous rank‐order survey, and more than 1, 200 responses were returned. The responses primarily came from periodontists, hygienists, general practitioners, dental students, and dental hygiene students. Results: "Periodontists surgically treat advanced gum and bone infection problems" was considered the most important statement in all of the cohorts. The least important statement considered by all was, "Periodontists are educators promoting health." Non‐periodontist dentists (NPDs) ranked the statement, "Periodontists perform dental implants and related procedures" less importantly ( P <0.001) than the periodontists. The non‐periodontist cohort (NPC), which includes NPDs and dental hygienists, ranked the statement, "Periodontists' treatments help general dentists and other specialists increase successful therapeutic outcomes" as second most important. Conclusions: The results of this survey indicate that periodontists ranked the placement of implants and their related procedures higher than the NPC. NPDs appear to value periodontists in treating the natural dentition for their patients. The NPC appreciates that periodontal therapy done by periodontists increases their therapeutic success for their patients.